Manufacturing of Camembert type cheese made from goat's and cow's milk and their mixtures - Katarina Tonković; Ljerka Gregurek; Rajka Božanić (Mljekarstvo)
The aim of this research was to examine the influence of goat's and cow's milk and their mixtures on the quality of the Camembert type cheese within 30 days of its preservation. Cheeses were made of a mixture of goat's and cow's milk in the following ratios: 0:100, 30:70, 50:50, 80:20 and 100:0. They were analysed on the twelfth and thirtieth day of the cheese production. The chemical analysis of milk for cheese production, as well as the chemical composition, pH and sensorial evaluation of cheeses have been determined. It has been proven that the chemical content and type of milk influencesm sensorial evaluation of cheeses and their shelf life. The analysed cheeses, after 12th day of processing, obtained better sensorial scores than those after the 30th day. Cheeses made of goat's milk have obtained the best sensorial evaluation, although their shelf life was shorter than the rest of the cheese samples made of cow's milk and mixtures of goat's and cow's milk. The chosen storage temperature (10-11 ºC) was not adequate for Camembert cheeses. Therefore, in order to prolong the shelf life above the 30-day-period and to preserve sensorial properties of the cheeses, the temperature should be lower, i.e. 5 ºC.